Permainan Edukasi Operasi Hitung Matematika Berbasis Multimedia pada SD STRADA VAN LITH II - Ceria, Natalia; Sutopo, Hadi (Institut Teknologi dan Bisnis Kalbis, 2020)
SD Strada Van Lith II is an elementary school that the early establishment of Strada societysince 1924, and has branches in central Jakarta, tangerang, bekasi and east jakata. SD Strada Van LithII is a branch of east jakarta, duren palm. The problems that occur are like using whiteboards, markers,guidebooks and others so that this study aims to provide a more enjoyable learning atmosphere in thegame world, especially games that are educative. The purpose of the study is to facilitate learning andproduce instructional media-based educational game in the form of software on mathematics subjectsthat can be used as an alternative media to play while learning. The research method used in thisresearch is Multimedia Development Life Cycle (MDLC). The results of this study are desktop-basedapplications, that this application can provide new solutions in terms of teaching and learning activitiesand provide positive feedback for SD Strada Van Lith II.